2018
DOI: 10.1111/imcb.12041
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity alters uterine NK activity through a functional KIR2DL1/S1 imbalance

Abstract: In pregnancy, uterine natural killer cells (uNK) play essential roles in coordinating uterine angiogenesis, blood vessel remodeling and promoting maternal tolerance to fetal tissue. Deviances from a normal uterine microenvironment are thought to modify uNK function(s) by limiting their ability to establish a healthy pregnancy. While maternal obesity has become a major health concern due to associations with adverse effects on fetal and maternal health, our understanding into how obesity contributes to poor pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 53 publications
5
33
0
Order By: Relevance
“…In accordance to previous studies, no significant differences in NKG2D expression were detected within total NK cells between the BMI groups (53,75,(84)(85)(86)(87). In contrast, other studies demonstrated altered NKG2D expression in obese individuals, although with conflicting results.…”
Section: Aside Of This the Expression Of The Activating Counterpartsupporting
confidence: 89%
“…In accordance to previous studies, no significant differences in NKG2D expression were detected within total NK cells between the BMI groups (53,75,(84)(85)(86)(87). In contrast, other studies demonstrated altered NKG2D expression in obese individuals, although with conflicting results.…”
Section: Aside Of This the Expression Of The Activating Counterpartsupporting
confidence: 89%
“…IL8, VEGF, placental growth factor (PGF) and CXCL10, also known as IP-10) ( 153 ). In uNK cells, expressing activating KIR2DS1 or KIR2DS4, HLA-C promotes uNK cell degranulation and secretion of granulocyte-macrophage colony-stimulating factor (GM-CSF) and tumor necrosis factor (TNF) ( 186 , 200 , 207 ). Production of these factors potentially impacts EVT biology (discussed below).…”
Section: Communication Between Invasive Trophoblasts and Uterine Natumentioning
confidence: 99%
“…In contrast, others describe an elevated number of total uNK cells or of the CD56 + /CD16 + subset in PE ( 230 , 231 ). More recently, research has identified pre-existing health conditions of the mother that associate with low-grade inflammation, like obesity, that potentiate uNK cell activity and modify how uNK cells interact with fetal MHC ligand ( 207 ). However, although the in utero environment likely shapes uNK cell processes, to date, hard evidence showing that aberrantly activated uNK cells in humans directly target trophoblasts for killing has yet to be clearly demonstrated.…”
Section: Can the Breakdown Of Maternal-fetal Tolerance Be Related To mentioning
confidence: 99%
“…Obesity dysregulates NK biology [201,[219][220][221][222], promoting a highly activated state [193,220,223]. Despite the critical importance of these cells in regulating placental establishment and development, only a few studies have examined the effect of maternal obesity on uNK activity [129,185,224]. There is conflicting evidence emerging from mouse models of DIO examining alterations on NKs within the utero-placental environment.…”
Section: Obesity-driven Uterine Immune Cell Dysfunctionmentioning
confidence: 99%